Estimating mortality attributable to alcohol or tobacco – a cohort study from Germany - Ulrich John; Hans-Jürgen Rumpf; Monika Hanke; Christian Meyer (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background Little is known about mortality from four disorder combinations: fully attributable to alcohol or tobacco, partly attributable to both alcohol and tobacco, to tobacco only, to alcohol only. Aim To analyze whether residents who had disclosed risky alcohol drinking or daily tobacco smoking had a shorter time to death than non-risky drinkers and never daily smokers twenty years later according to the disorder combinations. Methods A random adult general population sample (4,075 study participants) of a northern German area had been interviewed in the years 1996–1997. Vital status and death certificate data were gathered 2017–2018. The data analysis included estimates of alcohol- or tobacco-attributable mortality using all conditions given in the death certificate and alternatively the underlying cause of death only. Results Among 573 deaths, 71.9–94.1% had any alcohol- or tobacco-attributable disorder depending on the estimate. Risky alcohol consumption and daily tobacco smoking at baseline were related to disorders in the death certificate according to the combinations. Deaths with an alcohol- and tobacco-attributable disorder were related to risky alcohol consumption (subhazard ratio 1.57; 95% confidence interval 1.25–1.98) and to daily tobacco smoking at baseline (subhazard ratio 1.85; 95% confidence interval 1.42–2.41). Conclusion First, more than 70% of the deceased persons had one or more alcohol- or tobacco-attributable disorders. This finding suggests that total mortality seems to be the suitable outcome if potential effects of alcohol or tobacco consumption in a general population are to be estimated. Second, the relations of risky alcohol consumption and tobacco smoking with time to death speak in favor of the validity of alcohol- and of tobacco-attributable disorders in death certificates and of considering both alcohol consumption and tobacco smoking if attributable deaths are to be estimated.